Singapore’s Next Fighter Project: Why the Eurofighter Typhoon is out of the race - Chew, Alvin (2016)
DESPITE being the smallest nation in Asia, Singapore has one of the most modern air, land and naval forces in its region. Its defence budget, consistently in the range of 5% of its GDP, has been invested in state-of the-art technologies to boost its military capabilities and deter external threats.